Evolution of legal regulation of municipal service in the Republic of Lithuania and Ukraine - A. O. Murtishcheva (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of the formation and development of legislation on municipal service in the Republic of Lithuania. Individual factors that influenced the evolution of legal regulation of public service have been determined, in particular, the impact of adapting legislation to the requirements of the European Union at the stage of Lithuania's membership has been analyzed. The stages of the development of the legislation on the service have been singled out, the main novelties of the legal regulation of the institute under study at each of the stages have been analyzed. A conclusion has been made about a sufficiently centralized model of legal regulation, which provides for unified regulation of state and municipal service. Despite the fact that this model is determined by national characteristics, it is emphasized that the Republic of Lithuania successfully applies it in practice, and therefore the legislation in the field of municipal service is considered to be in line with European standards.